Occurrence of killer yeast strains in industrial and clinical yeast isolates - MARCELO E BAEZA; MARIO A SANHUEZA; VÍCTOR H CIFUENTES (Biological Research, 2008)
The secretion of proteinaceous toxins is a widespread characteristic in environmental and laboratory yeast isolates, a phenomenon called "killer system". The killer phenotype (K+) can be encoded by extrachromosomal genetic elements (EGEs) as double stranded DNA or RNA molecules (dsDNA, dsRNA) or in nuclear genes. The spectrum of action and the activity of killer toxins are influenced by temperature, salinity and pH of media. In the present work we determined the existence of K+ in a collection of S. cerevisiae and P. anómala yeasts isolated from environmental, industrial and clinical sources. The assays were performed in strains belonging to three yeast genera used as sensitive cells and under a wide range of pH and temperatures. Approximately 51 % of isolates tested showed toxicity against at least one sensitive yeast strain under the conditions tested. The K+ P. anómala isolates showed a wide spectrum of action and two of them had toxic activity against strains of the three yeast genera assayed, including C. albicans strains. In all S. cerevisiae K+ isolates an extrachromosomal dsRNA molecule (4.2 Kb) was observed, contrary to P. anómala K+ isolates, which do not possess any EGEs. The K+ phenotype is produced by an exported protein factor and the kinetics of killer activity production was similar in all isolates with high activity in the log phase of growth, decaying in the stationary phase.